2008
DOI: 10.1590/s0100-67622008000100017
|View full text |Cite
|
Sign up to set email alerts
|

Fertilidade e carbono do solo e uso da água pelo eucalipto numa topossequencia em Seropédica, RJ

Abstract: RESUMO -A variabilidade espacial de atributos físicos, químicos, biológicos ou pedogenéticos é citada como responsável por padrões encontrados na distribuição do C e nutrientes do solo. Numa toposseqüência típica da Baixada Fluminense (Planossolo Háplico -PL, Argissolo Amarelo -AA e Argissolos Vermelho-Amarelos -AV1 e AV2), buscou-se avaliar a influência da paisagem na distribuição de atributos químicos e no uso da água e o crescimento do Eucalyptus urophylla. Amostras de solo foram coletadas ao acaso em três … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
1
3
0
10
Order By: Relevance
“…Since water availability has been identified as a determining factor for the growth of eucalyptus in Brazil (Reis et al, 1985;Stape et al, 2004;Souza et al, 2006;Balieiro et al, 2008a;Stape et al, 2010), high yields can be expected in light soils in areas with favorable rainfall incidence and distribution. Stape et al (2004) observed that in the state of Bahia, the high rates of the efficient use of soil (2-35% clay) cultivated with eucalyptus are associated with regions that have low deficit of air vapor saturation and water stress.…”
Section: Planted Forestsmentioning
confidence: 99%
“…Since water availability has been identified as a determining factor for the growth of eucalyptus in Brazil (Reis et al, 1985;Stape et al, 2004;Souza et al, 2006;Balieiro et al, 2008a;Stape et al, 2010), high yields can be expected in light soils in areas with favorable rainfall incidence and distribution. Stape et al (2004) observed that in the state of Bahia, the high rates of the efficient use of soil (2-35% clay) cultivated with eucalyptus are associated with regions that have low deficit of air vapor saturation and water stress.…”
Section: Planted Forestsmentioning
confidence: 99%
“…According to Balieiro et al (2008), relief has a strong influence on soil chemical properties. Carbon stocks along a toposequence are associated with landscape position, clay content, and particle density.…”
Section: Introductionmentioning
confidence: 99%
“…CAMPOS et al, (2010) estudando uma topossequência em Manicoré -AM constataram que as variações do relevo favoreceram a presença de solos distróficos no topo alto e solos eutróficos no sopé de transporte. BALIEIRO et al (2008) evidenciaram que o relevo possui forte influência sobre a distribuição dos nutrientes ao longo de uma topossequência, concluindo que o relevo influencia fortemente nos atributos químicos do solo, corroborando com essa afirmação MEIRELES et al, (2012) constataram que a relação Fe livre/Fe total apresentou tendência de decrescimento em relação as parcelas implantadas ao longo de uma sequência topográfica, verificando ainda que algumas superfícies geomórficas situadas em diferentes posições no relevo diferem no grau de desenvolvimento da superfície. REIS et al, (2007) além de nutrientes, também provaram que ocorrem variações na constituição granulométrica e orgânica do solo.…”
Section: Figura 2 Porcentagem Geral De Cores Da Amostra Unificada Deunclassified